Creación del Restobar Luna Roja en la ciudad de Montalvo - Avilez Robalino, Karen Rocio (2020)
The present venture intends to determine the viability of the implementation of a “Red Moon” resto-bar in the city of Montalvo belonging to the province of Los Ríos; establishing methods and using strategies for the sale of food and beverages that will be offered in the business, analyzing the necessary investment to start with the project, the financing that is needed, the projection of the profits, and an analysis of the financial feasibility that will allow Determine the profitability of the project. Also carrying out the study of operational, technical, social and environmental feasibility.